Inclusive Theatres as Boosters of Well-being: : Concepts and Practices - Di Giovanni, Elena; Raffi, Francesca (Journal of Audiovisual Translation, 2022)
With the surge in media accessibility studies, researchers have explored the possibility of using psychological indicators to study modes of production, consumption, and reception of audiovisual and accessible media texts. However, most of the methodologies and measures applied so far tend to evaluate perception and/or reception in the short term, i.e., immediately after viewing media texts or attending live performances. This article moves from previous articles on inclusive theatres (Di Giovanni, 2021; Raffi, 2021) and sets forth to evaluate individuals’ reactions to inclusive activities in the medium to long-term. To this end, the concept of well-being becomes central, along with some of the measures and tools so far employed to measure it outside the realm of accessibility studies. Lay summary Media accessibility is the research area dealing with the theories, practices, and instruments that provide access to media products, services, and environments for people that cannot, or cannot properly, access that content in its original form. Media accessibility research has truly blossomed in the past years and has welcomed new, often not-so-close theoretical and methodological approaches. More recently, researchers have explored the possibility of using psychological indicators to evaluate perception and/or reception in the medium to long-term, i.e., the medium to long-term effects of inclusive practices in theatre and other media experiences. To this end, the concept of well-being becomes central, along with some of the measures and tools so far employed to measure it outside the realm of media accessibility studies. This article moves from previous studies on inclusive theatres, which place the people and their diverse abilities at the core, to prove that it is time to move beyond the well-established practices of feedback collection immediately or soon after a performance or event. By reporting on a two-month experiment with young people with sensory disabilities who were trained to be inclusive guides in theatres, our aim is to reflect on the impact of such events, and of participation, on people’s lives in the medium to long-term.